Green Accounting Analysis To Firm Value : Study On Metal And Mineral Companies - Purwanti, Adinda Rizqu; Handayani, Susi; Mohd Ali, Mazurina (International Economic Conference of Business and Accounting, 2024)
Over time, economy continue to expand swiftly and directly proportional to environmental issues. This study aims to find out how green accounting affects to firm value with quantitative approach. In this study, independent variables is green accounting proxied by environmental costs and environmental performance. Environmental cost measured by total environmental cost incurred divided by total operational expenses of company, whereas environmental performance measured by GRI 300 series. Dependent variable is firm value proxied by Tobin’s Q. This research was carried out between 2017 - 2021, with secondary data taken from sustainability reports and company’s annual reports. Population in this study was metal and mineral industry (B14) firms listed in IDX of 29 companies with purposive sampling methods. The result is, green accounting has no influence on firms value. This is due to green accounting does’nt have direct influence to firm value, but can provide greater long-term benefits in terms of operational efficiency, business sustainability, and reduced environmental risks.